New NGR-targeted shRNA-loaded Liposome Suppresses Glioma Growth - ZHAO Guanjian; ZHANG Xiang; CHENG Yuan; WANG Zhigang; HUANG Qin (Zhongliu Fangzhi Yanjiu, 2019)
Objective To prepare the new NGR-targeted shRNA-loaded liposome, and investigate its suppressing effect on orthotopic C6 glioma in rats. Methods (1) Liposome(lipo), the NGR-targeted liposome (lipo-NGR) and shBirc5-loaded lipo-NGR were prepared successively, and all kinds of products were characterized accordingly; (2) The targeting property of shBirc5-lipo-NGR was researched by immunohistochemical method in orthotopic C6 glioma rats model; (3) The tumor growth in treated rats was monitored longitudinally with MRI T2, and the survival time of each rat was recorded simultaneously. Results (1) We successfully prepared shBirc5-lipo-NGR whose size and zeta potential were (186.2±74.07)nm and (10.9±3.76)mV; (2) The Birc5 protein was significantly decreased in shBirc5-lipo-NGR group, compared with shBirc5-lipo group, shControl-lipo-NGR group and control group; (3) The control group exhibited an average tumor volume and growth rate 4.7 times greater than that in the shBirc5-lipo-NGR group on the 12th, 17th and 22th day(P < 0.05). The median survival times of the shBirc5-lipo-NGR, shBirc5-lipo, shControl-lipo-NGR and control groups were 30, 24, 22, 21 days, respectively. Conclusion We successfully prepare the new NGR-targeted shRNA-loaded liposome, and demonstrate its targeting property, obvious inhibitory effect on tumor growth and extending the survival time of orthotopic C6 glioma-bearing rats.